2019
DOI: 10.14233/ajchem.2020.22300
|View full text |Cite
|
Sign up to set email alerts
|

Poly Sulfoxyamine Grafted Chitosan as Bactericidal Dressing for Wound Healing

Abstract: In this study, sulfoxyamine derivative of chitosan was carried out by reaction with thionyl chloride and further treated with ammonia. FT-IR, 1H NMR, elemental analysis and DSC methods are used for confirmation of modification. The results revealed that the modified chitosan exhibits better water solubility than chitosan. The evaluation of the applicability of sulfoxyamine modified chitosan in the treatment of dermal wound in rats was performed by induction of transcutaneous wound. The antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The quaternization of chitosan can lead to materials with such improved antibacterial properties against several negative and Gram-positive bacteria [63][64][65][66]. It has also been reported that the addition of sulfoxyamine groups onto CS, produces a derivative with enhanced mucoadhesive and antibacterial properties [67]. Therefore, in this work, monomers carrying similar groups, such as tertiary amino groups and sulfoxide, have been chosen.…”
Section: Synthesis Of Cs Derivativesmentioning
confidence: 99%
“…The quaternization of chitosan can lead to materials with such improved antibacterial properties against several negative and Gram-positive bacteria [63][64][65][66]. It has also been reported that the addition of sulfoxyamine groups onto CS, produces a derivative with enhanced mucoadhesive and antibacterial properties [67]. Therefore, in this work, monomers carrying similar groups, such as tertiary amino groups and sulfoxide, have been chosen.…”
Section: Synthesis Of Cs Derivativesmentioning
confidence: 99%
“…Except for quaternary CS derivatives, it was found that when carboxyl groups were grafted on CS chains, such as in the case of O-carboxymethyl CS (CMCS), antibacterial properties were further enhanced [99]. The introduction of sulfoxyamine groups in CS resulted in a derivative with simultaneously enhanced mucoadhesive and antibacterial properties [107].…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…Modification was performed by our previous described method [14]. Chloro sulfoxy Chitosan was synthesized by mixing the 100 ml of pyridine with 10 gm of Chitosan.…”
Section: Modification Of Chitosanmentioning
confidence: 99%
“…Another class of agents is Quorum -sensing compound which potentially used for antimicrobial coating material to the Lens [13]. Other types of anti infective agents may be used to kill the infections organism or prevent them from causing infection [14].…”
Section: Introductionmentioning
confidence: 99%